Changes in the structure and properties of road bitumen during its thermal stabilization - N. I. Shestakov; N. V. Khokhlova; Yu. E. Vasiliev; U. O. Menkina (Vestnik MGSU)
Introduction. Petroleum bitumen is the main component of road surfaces, which play an important role in ensuring the safety and comfort of vehicle traffic. Over time, bitumen undergoes ageing, which leads to changes in its physical and chemical properties. Such changes cause a decrease in the quality of road surfaces, deterioration of their performance characteristics and reduction of durability. The analysis of research in the field of bitumen thermal stabilization, which is of great importance for optimization of technological processes at high temperatures, was carried out. The optimal composition of modified bitumen using stearic acid, industrial oil was determined.Materials and methods. Bitumen undergoes serious changes during technological processes, during the transition from the bulk to the film state under the influence of high temperatures. Thus, thermal stability of bitumen is an important condition for preserving its quality at all stages of its life cycle. The issue of bitumen thermal stabilization with the use of stearic acid T-18 in combination with industrial oil I-20, which lead to increased resistance from external factors, is considered. To establish the degree of influence of modifying components on bitumen properties, a two-factor rotatable experiment with varying the amount of industrial oil and stearic acid additives, was performed.Results. The compositions and properties of the obtained modified bitumen were studied. The analysis of the obtained results shows that the effect of stearic acid on bitumen penetration is about 6 times higher than the effect of industrial oil, while both components together have insignificant effect on the other studied properties of bitumen.Conclusions. In order to further study thermal stability on the optimal versions of bitumen compositions, studies on mass retention of bitumen films at temperatures from 160 to 220 °C were performed. According to the obtained results, it was found that the effectiveness of stearic acid is manifested at higher temperatures and reaches values up to 25 %.